Przestrzenne aspekty planowania rozwoju w krajach trzeciego świata - Gruchman, Bohdan (Wydział Prawa i Administracji UAM, 1970)
Development planning is growing in popularity among countries of the third world. However, this kind of planning pays little attention to regional dimensions of growth. There is a striking similarity of the said situation in the third world with that existing in the developed countries in their earlier stages of growth. Yet, strong arguments speak in favour of a different approach in this respect. The labour market of the developing countries has distinct regional features, which call for a separate treatment of each region. The economic and social infrastructure, necessary as a base for any acceleration of growth, must be analyzed in a regional context in order to be expanded in an efficient way and in the most desired direction. Finally, the process of industrialization, which no developing country can afford to bypass on its path to higher income requires a locational policy of agglomeration in order to generate external economics as means to overcome obstacles to faster development. In order to play the required role regional planning must be integrated with national development planning and be treated as equal to sectoral planning. It should cover all regions and not only those which offer the best prospects of positively influencing the rate of growth. This does not necessarily mean that the growth rate of all regions should be equal. Two stages of work are proposed for regional planning within the framework of national developmen planning: one concerned with project identification and the other with project selection.
Regional Dimensions of Development Planning in Countries of the Third World